MODEL PEMBELAJARAN INTERAKSI SOSIAL DALAM PEMBELAJARAN IPS DI SD/MI - Parni Parni (CV. ADIBA AISHA AMIRA, 2024)
Social studies learning is a science that must be taught to students at the elementary school level. This science is considered very important to learn so that they have a more mature readiness when they go into the field and have a direct role in society. To achieve good results, of course, it needs to be supported by a good learning process as well. To realise this, it is not easy, of course, requires a different learning model, in accordance with the objectives to be achieved. To choose a model of social studies learning in SD / MI must pay attention to a variety of things, among others, related to the emphasis on direct social values, and the learning model applied must be interesting, creative, innovative and in accordance with the situation and conditions that exist at the time of the learning process. A learning model is a plan or a pattern used as a guide in planning classroom learning or learning in tutorials. The learning model refers to the learning approach that will be used, including teaching objectives, stages in learning activities, learning environment, and classroom management. The learning model describes the steps or procedures that need to be taken to create effective, efficient and interesting learning activities. Learning models act as conceptual, management, communication tools, to analyse, design and create a good learning process. In general, learning models are unique and different in the steps and procedures used. However, learning models have the same principles in an effort to design a quality learning programme. Learning model refers to the learning approach that will be used, including teaching objectives, stages of learning activities, learning environment, and classroom management. This means that with these learning models teachers can help students to get or acquire information, ideas, skills, ways of thinking, and expressing their own ideas. In addition, they also teach them how to learn. Finally, each model requires a different management system and learning environment. Each approach assigns different roles to students, to the physical space, and to the social system of the classroom. One of the models used in social studies learning is the social learning model, because the social learning model is one of the models that emphasises relationships with the community or other people.